Multilingual HIV/AIDS terminology - Department of Arts and Culture (Department of Arts and Culture, 2013)
The HIV and Aids project was implemented by the National Terminology Services (NTS) of the Department of Arts, Culture, Science and Technology (DACST) in the early 90’s. The original list comprised about 400 term entries and was compiled by the then Biological and Agricultural Sciences internal project team. NTS terminologists supplied equivalents in their target languages in consultation with subject field experts, and used other available sources of information. In some languages it proved to be very difficult to document appropriate terminology. This was due to the lack of sufficient resources, and the fact that this was still a relatively new and specialised field. The purpose or aim of the HIV and Aids project is to promote communication between the general public and doctors, nurses, clinics and health professionals. This includes informing and educating the public of South Africa about this pandemic, its symptoms and HIV-associated diseases and related infections in a typical South African context. A consultative workshop was organised during the 1999/2000 financial year to try and finalise the provision of term equivalents in all the other 10 official languages. Challenges were identified during the workshop, and due to time and budgetary constraints the list was never finalised and disseminated to the public. Due to changes and new developments in this specific field over time, a need was identified to review the ground text. An additional 300 terms were added to the original list in collaboration with the Department of Health (DoH). Currently, the term list consists of 749 term entries with equivalents in all 10 official languages. The Terminology Technical Committees of the National Language Bodies (NLBs), created by the Pan South African Language Board (PanSALB), verified the coined terms. They gave their stamp of approval in principle, for the dissemination of the terminology to the general public. This multilingual list of core terms used in HIV and Aids education needs to be seen as a contribution to the campaign against HIV and Aids.
Department of Arts and Culture: Republic of South Africa